Investigations on the interactions between encapsulants and probiotics - Goh, Darilynn Jia Wei (Nanyang Technological University, 2021)
Probiotics have been proven effective in improving the health of both animals and humans through mechanisms such as the modulation of the intestinal microbiota. Microencapsulation technology plays a crucial role in maintaining the viability of probiotics. Encapsulants act as a protective barrier to probiotics and can withstand the surrounding harsh environment. However, the interactions between encapsulants and probiotics have often been largely overlooked which have hindered its potential applications. In this report, we aim to identify synergistic synbiotics and examine the interactions between commonly used probiotics and encapsulants. We first selected the encapsulants to be tested which are mainly polysaccharides. The polysaccharides were degraded using HCl acid hydrolysis and H2O2 oxidative degradation, and the shifts in molecular weight were characterized using Gel Permeation Chromatography (GPC). We then went on to investigate the growth boosting effects of different concentrations of polysaccharides and oligosaccharides on two probiotic strains, namely Lactobacillus rhamnosus GG (LGG) and Lactobacillus plantarum 299v by comparing the optical densities of the bacteria cultures. We confirmed that glucose, as evidenced in the literature, was the most preferred saccharide to be utilized by the probiotic strains in both aerobic and anaerobic conditions. Other saccharides also showed potential to be utilized by probiotics, but repetition of the experiments is needed to draw a better conclusion. We also investigated freeze-drying and ethanol precipitation as the methods to recover polysaccharides from solutions and concluded that both methods are effective, and the resultant products had little shifts in the chromatography. Autoclaving was used to sterilize alginate and kappa-carrageenan. From the results obtained after autoclaving, we gathered that autoclaving causes degradation of polysaccharides and should be minimised in future experiments. Further studies that remain to be done include fine-tuning of the degradation conditions of polysaccharides, repetition of in vitro selective modulatory assay and confirmation of synergistic synbiotic combination using gas-chromatography mass spectrometry (GC-MS).